Acceleration of Monte Carlo modeling of light transport in turbid media; an approach based on hybrid, theoretical and numerical, calculations - Di Rocco, Hector Omar (2009)
A novel method to accelerate Monte Carlo (MC) simulations of photon migration in turbid media is presented. It is specifically suited for transillumination studies in slab geometries including some deep inhomogeneity. Propagation up to the inhomogeneity, at a given depth S1, is replaced by theoretical calculations using well established models. Then, photon propagation is continued inside the complete slab using MC rules until detection or absorption occurs. We report improvements in speed in factors up to approximately 10; the deeper the inhomogeneity, the larger the improvement. Examples are given showing that information remains unchanged with respect to pure MC simulations.